For a few dollars more - Grimaldi, Alberto; Leone, Sergio; Metro Goldwyn Mayer Home Entertainment ([Santa Monica, CA : Metro Goldwyn Mayer Home Entertainment, 1998)
Two bounty hunters in the Southwest join forces to try and collect the $10,000 reward money for the head of a sadistic outlaw known as Indio
Title from title screen
Cast: Clint Eastwood, Lee Van Cleef, Gian Maria Volonte
DVD format
In Chinese, English, Japanese or Italian with optional Korean, Japanese, English, Chinese or Thailand subtitles
Keywords: Bounty hunters -- Drama; Outlaws -- Drama; Feature films; Western films